Studying English Literature in the Transnational University - Miller, J. (Surfaces)

(untitled) (Les Presses de l’Université de Montréal, 1996)
Against the backdrop of the end of the Cold War, the decline of the Nation-State, the globalization of economies and research efforts, the radical transformations being brought about by new communications technologies, and the shift in funding from government sources to transnational corporations, this essay examines the role of literary studies and the humanities in the context of the emerging transnational university.